Financial Literacy: Unravelling The Interplay of Psychological Dynamics and Social Influences on Financial Behaviours - Dian Wismar'ein; Linda Putri Nadia; Indah Puspita Maharani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2026)
Purpose – This study investigates key determinants of personal financial management behaviour among Indonesian millennials, focusing on the roles of financial literacy, attitude toward money, locus of control, and financial socialisation sources, including parents, peers, media, and social media.Methodology – Data were collected through an online questionnaire using purposive sampling and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM).Findings – The results show that financial socialisation, parental socialisation, social media, and peer and media influences positively affect millennials’ attitudes toward money and financial management behaviour. External locus of control does not directly influence financial behavior but indirectly mediates the effects of financial socialization and peer and media influence. Attitude toward money mediates the influence of family financial socialization and peer and media exposure. In contrast, financial literacy mediates the impact of family financial socialization, peers, media, and locus of control on financial behavior.Originality/Novelty – This study offers an integrated model that combines psychological factors and diverse financial socialization agents to explain millennial financial behavior. This area remains underexplored in the Indonesian context.Implications – The findings highlight the need for targeted financial education initiatives that strengthen socialization pathways and enhance financial literacy to improve millennials’ financial management practices.